THE IMPACT OF PRINCIPAL LEADERSHIP ON STUDENT ACHIEVEMENT - Thome, Fredrik Hendrik (Postgraduate School, Universitas Nusa Cendana, 2024)
The quality of student learning outcomes is a barometer of the success of an educational institution. This quality is closely related to teacher performance and the principal's leadership style, known as management strategy. This paper is a research report on the relationship between principal competence, teacher performance and student learning outcomes in primary schools in Cluster XVIII, Kupang City. Using the methods of observation, interview and documentation study, which are part of the qualitative research steps, the relationship between principal's management competence and student learning outcomes is revealed. The results of data analysis indicate that there is a strong relationship between principals' competence in managing the educational institutions they lead and their students' learning outcomes. For this reason, it is recommended that every principal, as a leader, must have managerial competence that includes 2 dimensions, namely managerial competence dimensions and supervisory competence dimensions, so that student learning outcomes can be achieved.